San????es pol??ticas em mat??ria tribut??ria - Franco J??nior, Nilson Jos?? (2016)
This dissertation discusses the topic political sanctions on tax matters. Performs a general approach on tax penalties, its features, functions and species. Analyzes the concepts and definitions of those restrictive measures that are recognized by the Supreme Court as illegitimate, highlighting how consolidated in patriotic courts through sumulares set out in paragraph 70, 323 and 547. It also makes an analysis of those restrictive sanctions law, because of their purpose, the Supreme Court recognizes as legitimate. Are then analyzed all the precedents that gave rise to the guiding overviews the recognition of tax political sanctions, bringing to discuss the case studies and their particularities that made firmasse that understanding. After analyzed the precedents and their motives, the rights and guarantees that are considered constitutional basis for the recognition of tax policy sanction is analyzed and therefore deserving the jurisdictional control of the judiciary as a guarantee of compliance with these precepts. Finally, it concludes with previous studies of the Supreme Court, which recognized legitimate and illegitimate tax penalties, enabling a comparison between the decisions.